Towards A Monetary Union in the Economic Community of West African States (ECOWAS): Prospects and Challenges" - Kode, David Ebung (My University, 2006)
This study aims at highlighting the politics of international cooperation with respect to monetary integration in West Africa. Monetary integration was envisaged in the Economic Community of West African States (ECOWAS) when the organization was formed in 1975. Two decades after its formation, it was realized by member states that limited success had been achieved as far as the objectives of the organization were concerned. As a result, the ECOWAS Treaty was revised and significant decisions were made in 1993, and the call for a monetary union was reiterated. Factors which could have worked against the formation of a monetary union prior to 1993 changed in favour of monetary cooperation. The adoption of the Euro in the European Union and more especially by France, weakened the symbolic link of the CFA Franc zone to France, and to an extent reduced the French stigma, which had hitherto discouraged Anglophone countries from participating in an expanded monetary union with their Francophone counterparts. The democratic transition of Nigeria and the accession to power of a new leader who has shown commitment to regional integration, improved cooperation arrangements among ECOWAS states in working towards the formalization of a monetary union. The transformation from the Organization of African Unity (OAU) to the African Union (AU) and its strategy of creating a common African currency as well as the emergence of the New Partnership for Africa’s Development (NEPAD) provided extra motivations for African states to show more commitment towards integration. Based on the above factors, several positive steps have been taken towards the formalization of a monetary union in the community. The West African Monetary Zone (WAMZ) was realized in 2000 and more importantly, the West African Monetary Institute (WAMI) was created and started operating in the same year. The Institute was created to prepare the groundwork for the creation of the West African Central Bank. The above mentioned factors increased the prospects of forming a monetary union in the community but several challenges still remain. First there is the problem of the asymmetric nature of the economies in the region. Secondly, political instability is a major factor that militates against the formation of such a union. Domestic political instability in Nigeria, which is heightened by ethnic and religious differences as well as the asymmetric nature of her economy in relation to those of other states in the region, makes it difficult for a monetary union to revolve around her. This research project is centered on Treaties, statistical analysis, theories and concepts and literature from economic and financial institutions. We conclude by stating that the analysis here reflects the situation on the ground and provide lessons to member states of the community, prospects for monetary integration would be further improved if member states work coherently to overcome such challenges.
Student Number : 0414488P - MA research report - School of Social Sciences - Faculty of Humanities
Keywords: politics of international cooperation; monetary integration; West Africa; Economic Community of West African States; ECOWAS